PENGARUH PANJANG PIPA ALUMINIUM KONDENSATOR DAN KETEBALAN AIR PADA PERENCANAAN DISTILATOR TEPAT GUNA - Abdu Fadli Assomadi (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2008)
Communities in coastal areas use rain water and ground water to meet the needs of clean water. Precipitation occurs only during the rainy season. The ground water is brackish because of seawater intrusion. This is a problem for this community. Therefore, appropriate water treatment technology is needed especially during the dry season. This research was aimed to measure the influence of the length of long aluminium condenser pipe and the water thickness to the brackish water distillation yield. Variables which were tested were water thickness of 0.5, 1 and 1.5 cm and the length of aluminium pipe condenser of 260, 320, and 380 cm. Two types of glass roofs of were applied. One roof was flat, and the other had an of angle 600. The results showed that the sloped roof produced the highest water volume, with an average of 1045 mL/m2. The percentage of condensate volume produced from distillator with pipe lengths of 260, 320, and 380 cm were 50%, 96%, and 98.3% respectively. Water thickness of 1 cm yielded the highest water volume of 1102.1 mL/m2. The highest distillation rate was 0.167 L/m2 hour.